TLR4 Deficiency Exacerbates Biliary Injuries and Peribiliary Fibrosis Caused by Clonorchis sinensis in a Resistant Mouse Strain - Yan, Chao; Wu, Jing; Xu, Na; Li, Jing; Zhou, Qian-Yang; Yang, Hui-Min; Cheng, Xiao-Dan; Liu, Ji-Xin; Dong, Xin; Koda, Stephane; Zhang, Bei-Bei; Yu, Qian; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Mice with different genetic backgrounds have various susceptibilities to infection with Clonorchis sinensis, although the mechanisms underlying are largely unknown. Toll-like receptor 4 (TLR4) as one of the most important pattern recognition receptors (PPRs) is essential for the invasion, survival, pathogenesis, and elimination of worms. The roles played by TLR4 in C. sinensis infection may vary due to the different genetic backgrounds of mice. In the present study, a relatively resistant mouse strain-C57BL/10 to C. sinensis was used for investigation on the possible roles of TLR4 in the biliary injuries and peribiliary fibrosis. TLR4 wild type (TLR4wild) and TLR4 defective (TLR4def) mice were orally infected with 50 metacercariae of C. sinensis, and all C. sinensis-infected mice and non-infected groups were anesthetized on day 28 post-infection. The liver and serum from each mice were collected for assessment of the biliary injuries and biliary fibrosis. Meanwhile, hepatic leukocytes were isolated and detected for the activation of M1 or M2 macrophage using flow cytometry. The hepatic type 1 immune response and type 2 immune responses -relative molecues were also evaluated using ELISA and quantitative PCR. The data showed that TLR4def aggravated liver inflammatory cell infiltrations, bile duct proliferation, biliary and hepatocellular injuries, and ECM deposition in C. sinensis-infected mice, compared with TLR4wild mice when they were intragastrically administered with the same amounts of C. sinensis metacercaria. Furthermore, the M2-like macrophages and type 2 immune resposnes were significantly predominant induced in TLR4defmice, compared with that of TLR4wild mice following C. sinensis infection. But the type 1 immune responses were significantly decreased in TLR4def mice, compared with TLR4wild mice after C. sinensis infection. These data demonstrate that TLR4 deficiency exacerbates biliary injuries and peribiliary fibrosis caused by C. sinensis in C57BL/10 strain mice, which is contributed by augments of type 2 immune responses and decrease pro-inflammatory responses.